Techno-Economic Analysis of On-Grid Rooftop PV Systems Integrated with BESS for Meeting the Energy Needs of Residential EV Home Charging Customers in Jakarta - Sonia Eka Putri; Akhmad Herman Yuwono; Eko Adhi Setiawan (International Journal of Recent Technology and Applied Science (IJORTAS), 2025)
The growing adoption of electric vehicles (EVs) in Indonesia, especially in urban areas like Jakarta, is expected to increase household electricity consumption. Rooftop solar photovoltaic (PV) systems integrated with battery energy storage systems (BESS) offer a promising solution to supply clean and self-sufficient energy. This study aims to assess the techno-economic feasibility of on-grid rooftop PV systems combined with BESS for residential EV home charging in Jakarta under various export compensation schemes and cost scenarios. Using the HOMER Grid software, three system configurations were simulated: grid-only, PV + BESS without export, and PV + BESS with 65% export compensation. The optimal setup consists of an 8.97 kW PV and 5 kWh BESS, yielding an internal rate of return (IRR) of 18%, a levelized cost of energy (LCOE) of $0.042/kWh, and a payback period of 5 years. Sensitivity analysis highlights that a minimum export compensation of 40% and projected cost reductions, especially in BESS are critical for long-term viability. A larger system with 15 kWh BESS becomes economically feasible after 2028, achieving a 16% IRR. Integrating rooftop PV and BESS could reduce CO₂ emissions by up to 9,932 kg/year compared to a grid-only system. Policy recommendations include export compensation of at least 40%, targeted investment incentives, and co-investment models involving PLN, PV providers, and EV dealers.